Implementasi Algoritma FIFO Dalam Sistem Pengaduan Online Berbasis Mobile Pada Dinas Lingkungan Hidup Kabupaten Sleman - Nurochman, Rizal Sofyan; Widodo, Tri (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2025)
Increasingly complex environmental problems and increasing public awareness of environmental issues require easy facilities for making complaints about environmental problems, so that they can be immediately followed up by the relevant agencies. This research develops an online complaint system for the Environmental Agency using the Rapid Application Development (RAD) method which emphasizes rapid and iterative system development. The mobile application was developed using React Native, the admin web application using React, and Firebase as Backend-as-a-Service (BaaS). The result of this research is a mobile application that makes it easy for people to complain about problems with data in the form of location details, descriptions, and photos or videos as supporting evidence. The web application makes it easy for admins to manage and follow up on complaints by applying the FIFO algorithm for complaint management. The application also helps the community monitor the complaint handling process to see the progress of handling the problem complained about.